Optimal selection of temperature areas by juvenile cod (Gadus morhua L.) in the Barents Sea modelled by dynamic optimisation - Kristiansen, Tore S.; Michalsen, Kathrine; Jacobsen, Jan Arge; Huse, Irene (ICES Journal of Marine Science, 2001)
The trade-off between growth rate in areas with different temperatures and predation rates was modelled for juvenile cod living in the Barents Sea by a dynamic optimisation model. The choice of optimal temperature area of a juvenile (1-group) cod growing from a start weight (50 g, 15 cm) to a size refuge (640 g, 40 cm) was modelled for two scenarios with distributions of predators (4+ groups cod) similar to those observed in the Barents Sea in February 1990 and 1994, respectively, and without food limitations. The model predicted that when there was an overlap in distribution between large cod and younger cod (0–3 group), the younger year classes would move to areas with lower temperature and less predators, offering higher survival rates. Fish predators forced the prey to inhabit less optimal areas, and both growth and survival rates fell in comparison with a scenario with fewer fish predators (cannibals) and less overlap. Increased fish predator density increased these effects, and the juveniles would stay in colder water for a longer period and their growth rate would be further reduced. Higher mortality, independent of area and size, made it more profitable to stay in warmer water, leading to higher growth but increased mortality rates.